A facile one-pot multi-component synthesis of novel adamantine substituted imidazo[1, 2-a]pyridine derivatives: identification and structure–activity relationship study of their anti-HIV-1 activity. Issue 97 (5th October 2016) - Tazeem,; Han, Xin; Zhou, Qingjun; Wei, Jingchen; Tien, Po; Yang, Guichun; Wu, Shuwen; Dong, Chune
Abstract : A series of adamantine substituted imidazo[1, 2- a ]pyridine derivatives were developed through a one-pot multi-component Groebke–Blackburn–Bienaymé reaction, among them several compounds were identified to be the potent inhibitors against HIV-1 cells. Abstract : In this study, a series of adamantine substituted imidazo[1, 2- a ]pyridine derivatives were designed and synthesized through a one-pot multi-component Groebke–Blackburn–Bienaymé reaction. Their anti-HIV activities were evaluated using an HIV-1IIIB /TZM-bl indicator cell culture system, in which compounds19d, 19e and19m were found to be the most potent inhibitors with EC50 values of 0.048, 0.061 and 0.077 μM, respectively. Furthermore, the modeling results provided valuable insight into how compound19d gave good efficacy against HIV-1 cells.